Diagnostic Fine Needle Aspiration Cytology of Malignant Testicular Sertoli Cell Tumor with Cutaneous Metastasis in an Adult - Gupta, Anshu; Gupta, Anjali; Bhardwaj, Priyanshi (Indian Journal of Case Reports, 2026)
Sertoli cell tumors (SCTs) of the testis are sex cord stromal tumors. These are very rare and usually benign. Malignant behavior is observed in 10% of such tumors. The occurrence of metastasis in such cases is extremely rare, with few cases reported in the literature till now. We present an unusual case of cutaneous metastasis of a malignant SCT in a 44-year-old male, diagnosed on fine needle aspiration cytology of a scrotal nodule, 6 months after radical orchidectomy for the primary tumor. The cytopathological findings of the scrotal nodule were correlated with the histopathology of the primary tumor and complemented with an immunocytochemical study that showed cytokeratin and vimentin positivity. Thus, cytopathological features along with immunocytochemical study provide an accurate diagnosis of the rare entity, when seen at metastatic sites also.